2012
DOI: 10.1038/npp.2012.15
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Hedonic Reaction to Reward and Incentive Motivation in an Animal Model of the Negative Symptoms of Schizophrenia

Abstract: We previously showed that mice that selectively and reversibly overexpress striatal D2 receptors (D2R-OE) model the negative symptoms of schizophrenia. Specifically, D2R-OE mice display a deficit in incentive motivation. The present studies investigated the basis for this deficit. First, we assessed whether hedonic reaction to reward is intact in D2R-OE mice. We assessed licking behavior and videoscored positive hedonic facial reactions to increasing concentrations of sucrose in control and D2R-OE mice. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 46 publications
(71 reference statements)
8
118
1
Order By: Relevance
“…In this task, mice must work increasingly harder to earn successive food rewards, and D2R-OE mice quit after earning fewer rewards than control littermates. In another assay, we found that D2R-OE mice also exert less effort and earn fewer rewards in a current choice paradigm in which the mice can press a lever to obtain a preferred reward (milk) or, instead, consume less preferred food (regular home cage chow) without any work requirement (17). Incentive motivation can be manipulated by modulating DA receptor activity in the NAc (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this task, mice must work increasingly harder to earn successive food rewards, and D2R-OE mice quit after earning fewer rewards than control littermates. In another assay, we found that D2R-OE mice also exert less effort and earn fewer rewards in a current choice paradigm in which the mice can press a lever to obtain a preferred reward (milk) or, instead, consume less preferred food (regular home cage chow) without any work requirement (17). Incentive motivation can be manipulated by modulating DA receptor activity in the NAc (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive phenotypes of D2R-OE mice include deficits in working memory tasks, behavioral flexibility, conditional associative learning, and timing (11)(12)(13)(14). D2R-OE mice also exhibit phenotypes similar to the negative symptoms of schizophrenia: a deficit in incentive motivation, without disruption of hedonic processes (13,(15)(16)(17). We previously reported that these behavioral deficits in striatal D2R-OE mice are accompanied by changes in cortical DA function (11,18).…”
mentioning
confidence: 99%
“…In comparison, striatal DA D 2 R overexpression has produced both increases (Trifilieff et al, 2013) and decreases in food-reinforced responding (Drew et al, 2007;Simpson et al, 2011;Ward et al, 2012), with outcomes possibly depending on age of induction, degree of overexpression, and selectivity of the overexpression for subregions of the striatum (Trifilieff et al, 2013). Finally, diet-induced obesity in rats was associated with reduced striatal DA D 2 R expression and striatal DA D 2 R reduction was associated with the development of consumption of high-fat, high-sugar foods that was resistant to suppression by electric-shockassociated stimuli (Johnson and Kenny, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Animals were first trained to consume evaporated milk from the liquid dipper, which was centrally located between two retractable levers in standard testing chambers (ENV307W, MedAssociates). The mice were then trained to press the lever to obtain rewards on a continuous reinforcement (CRF) schedule as described previously (Ward et al 2012b). Each CRF session ended after 60 rewards or 60 min, whichever occurred first.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%